Diffuse large B-cell lymphoma—treatment approaches in the molecular era - Roschewski, Mark (Nat Rev Clin Oncol, 2013)
Diffuse large B-cell lymphoma (DLBCL) is an aggressive B-cell non-Hodgkin lymphoma that affects patients of all ages with a wide range of clinical presentations. Although DLBCL is curable even in advanced stages, up to one-third of patients will not achieve cure with initial therapy. In the modern era of rituximab-based therapy as the first-line treatment, the prognoses of patients who require salvage therapy are poor and most will eventually succumb to their disease. Insight into the complex molecular circuitry of DLBCL reveals a diverse range of somatic mutations and aberrant intracellular signalling pathways that characterize distinct molecular subsets of the disease. The next major breakthrough in DLBCL therapy during this ‘molecular era’ of disease definition will be the identification of combinations of novel agents that target the oncogenic drivers of these subsets. Well-conducted clinical trials, with translational molecular investigations, will be essential to achieve the goal of precision medicine and expand the number of patients with DLBCL who achieve a cure.